SISTEM INFORMASI PERHITUNGAN HARGA POKOK PENJUALAN PRODUK PAKET DENGAN MENGGUNAKAN METODE NILAI PENJUALAN RELATIF PADA COUNTER IQYU CELL - Ronald Sugianto; Sudirman; Afifah (JTRISTE, 2018)
Iqyu Cell Store is a store engaged in the sale of mobile accessories, and active speakers. Generally, the process of calculating the cost of goods sold for each item and product package in the trading business is currently done manually and there is no recording process after calculating and also during this trading business still does not know the exact cost of goods sold for each item and package product, This can result in high or low selling prices of each item and also the package product provided. The method of relative sales value is one method of calculating cost of goods sold that can be used as a method to determine the selling price. The purpose of this study is to design an information system for calculating the cost of goods sold by using the relative sales value method. With the system of calculating package cost of goods sold, the owner can make this system as a means of calculating the cost of goods sold in the package which will become the benchmark for determining the right selling price, and also can find the maximum percentage decrease in selling price of package products to prevent low the selling price given.